COMPARATIVE STUDY BETWEEN CLOSE REDUCTIONS VERSUS CLOSE REDUCTION WITH K-WIRE FIXATION IN COMPLETELY DORSALLY DISPLACED DISTAL RADIAL METAPHYSEAL FRACTURE, IN CHILDREN AND ADOLESCENT (Iraqi Journal of Medical Sciences, 2016)
Background: Distal Fracture of the radius in children-sometimes (erroneously) called ‘Juvenile colles’ is among the commonest sites of childhood fractures. Cases with completely dorsally displaced fracture of distal radial metaphysis were collected, evaluated, and treated with either closed reduction or closed reduction with K-wire fixation.Objective: is to evaluate the advantage of percutaneous K-wire with cast immobilization over cast immobilization alone in management of displaced distal metaphyseal fracture in children and adolescent below 15 years with respect to maintenance of reduction and Join Motion.Methods: In this study 34 children all sustained completely displaced distal metaphyseal fracture of the radius were divided into two groups:Group A consist of 16 children (10 boys and 6 girls), with a mean age 7.9 years. Group B consist of 18 children (11 boys and 7 girls), with a mean age 8.6 years.In both groups reduction was achieved by closed method under general anaesthesia and image intensifier and reduction was easily achieved beyond 70% of cortical contact and less than 15°of angulation.For group A: the fracture was immobilized by complete above elbow cast. For Group B: the fracture was immobilized by insertion of a percutaneous K-wire across the fracture with complete above elbow pop cast. The patients (in both groups) were discharged from the hospital in the second postoperative day. The patients in group A reviewed once weekly for the first 3-4 weeks with anteroposterior and lateral radiographs and four children (25%) of this group was complicated by redisplacement of the fracture, three of them required remanipulation under general anaesthesia, while in group B the complications rate were low regarding redisplacement and there was no need for remanipulation. These patients were reviewed every 3 weeks and X-ray exposure was low. The union rate in both groups was the same.Results: Risk of displacement was greater in group A (25%) compared with no displacement in group B. Pin track infection in group B occur only in one case (5-6 %) regarding limitation of pronation supination and dorsiflexion (as compared with uninjured side )in both groups ; for group A wrist flexion 35°(58.3% of normal range )while pronation- supination was 40° (44.4% of normal range ) for group B wrist flextion 40°( 66.4% of normal range ) and pronation _supination was 55°( 61.1% of normal range.Conclusion: supplementary percutaneous K –wire fixation results in better maintenance of alignment, reduces the need for follow up radiographs and the need for further procedures to correct loss of position. Keywords: completely displaced fracture left radius, cast, K-wire.
Keywords: completely displaced fracture left radius; cast; Kwire